Adolescent tobacco use practices and user profiles in a mature Swedish moist snuff (snus) market: Results from a school-based cross-sectional study. Issue 7 (November 2016) - Lund, Ingeborg; Scheffels, Janne
Aims: The aim of this work was to study the diversity of tobacco use among Norwegian adolescent tobacco users and to investigate how different user groups compared with each other in terms of lifestyle and risk correlates. Swedish moist snuff (snus) use has increased dramatically in Norway over the last few years and is now more prevalent than smoking in younger age groups.Methods: The participants were 736 15-year-old tobacco users obtained from a large school-based cross-sectional survey (response rate 73%). Leisure time activity and risk behaviour factors were extracted by principal components analysis. Associations between tobacco use, leisure activities, risk behaviours, alcohol use and sex were studied bivariately and by logistic regression.Results: In total, 41.5% of the tobacco users were dual users (smokers and snus users). Problem behaviour and risk-taking lifestyles were associated with tobacco use frequency and high-frequency dual use, with a low risk profile for all types of occasional users (snus, cigarettes or dual users), a medium risk profile for all types of daily single-product users, including those who occasionally used the other product (i.e. dual users) and a high-risk profile for those who used both products daily (daily dual users). Conclusions: Fragmented use patterns in adolescence undermine the dichotomy often applied between smokers and snus users. For associations with lifestyle and risk correlates, use frequency and high-frequency dual use seem to be more important than the choice of product.